2018
DOI: 10.1364/oe.26.008059
|View full text |Cite
|
Sign up to set email alerts
|

125 Gbit/s discretely tunable InP-on-silicon filtered feedback laser with sub-nanosecond wavelength switching times

Abstract: Abstract:A heterogeneously integrated InP-on-silicon fast tunable filtered feedback laser is demonstrated. The laser device consists of a main Fabry-Pérot cavity connected to an integrated arrayed waveguide grating of which the outputs form external cavities in which semiconductor optical amplifiers can be switched to provide single-mode operation and tunability. The laser can operate at four different wavelengths whereby switching between each wavelength channel is done within one nanosecond. For each wavelen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…A schematic is shown in Fig. 4(a) [8]. The laser consists of a main Fabry-Pérot (FP) cavity with two partially reflective broadband SOI DBR mirrors (denoted as DBRFF and DBROut respectively).…”
Section: Laser Structurementioning
confidence: 99%
“…A schematic is shown in Fig. 4(a) [8]. The laser consists of a main Fabry-Pérot (FP) cavity with two partially reflective broadband SOI DBR mirrors (denoted as DBRFF and DBROut respectively).…”
Section: Laser Structurementioning
confidence: 99%
“…3,4) For example, next-generation passive optical network 2 (NG-PON 2) requires sub-second timescale wavelength tunable lasers to minimize the network delay. [5][6][7] To date, several kinds of high-speed tunable lasers have been developed [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] However, these lasers have some drawbacks, such as poor single-mode stability and the need for a complex fabrication process. Tunable distributed feedback (DFB) laser array (TLA) is suitable for the nextgeneration optical network because of free mode-hopping and a relatively simple DFB design.…”
Section: Introductionmentioning
confidence: 99%
“…Laser sources integrated in PIC can be achieved using various integration routes including flip-chip bonding [4], benzocyclobutene (BCB) bonding [5,6], direct wafer bonding, and epitaxial growth. Since Fang et al demonstrated the first hybrid silicon evanescent laser with a direct bonding process in 2006 [7], the hybrid silicon laser could run under contact conditions, They reported an electrically pumped distributed feedback (DFB) silicon evanescent laser in 2008 [8], and a low threshold and high speed short cavity DFB hybrid silicon laser was achieved in 2014 [9].…”
Section: Introductionmentioning
confidence: 99%